eCM 2012
DOI: 10.22203/ecm.v024a25
|View full text |Cite
|
Sign up to set email alerts
|

An electrospun polydioxanone patch for the localisation of biological therapies during tendon repair

Abstract: Rotator cuff tendon pathology is thought to account for 30-70 % of all shoulder pain. For cases that have failed conservative treatment, surgical re-attachment of the tendon to the bone with a non-absorbable suture is a common option. However, the failure rate of these repairs is high, estimated at up to 75 %. Studies have shown that in late disease stages the tendon itself is extremely degenerate, with reduced cell numbers and poor matrix organisation. Thus, it has been suggested that adding biological factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…This is close to commonly sutured electrospun poly(caprolactone) (PCL) (164 N · mm −2 ) and several times greater than poly(ether urethane urea) (PEUU) blends (35–59 N · mm −2 ) which were sutured for in vivo fixation . PDO is a FDA‐approved material used for sutures that resorb within 6 months or faster for fibers with high surface area . In vitro culture of HUVECs on electrospun PDO fibers also demonstrate good attachment as indicated by sprawled morphology (Figure c and f).…”
Section: Resultssupporting
confidence: 56%
“…This is close to commonly sutured electrospun poly(caprolactone) (PCL) (164 N · mm −2 ) and several times greater than poly(ether urethane urea) (PEUU) blends (35–59 N · mm −2 ) which were sutured for in vivo fixation . PDO is a FDA‐approved material used for sutures that resorb within 6 months or faster for fibers with high surface area . In vitro culture of HUVECs on electrospun PDO fibers also demonstrate good attachment as indicated by sprawled morphology (Figure c and f).…”
Section: Resultssupporting
confidence: 56%
“…Generally, they can be divided into three major groups including biological (natural), synthetic and hybrid materials 12,41,42 . Biological materials such as collagen, elastin, gelatin, chitosan, albumin, alginate, fibrin and chondroitin sulphate have been shown to be effective in tendon healing 36,40,43,44 .…”
Section: Basic Materials Of the Scaffoldmentioning
confidence: 99%
“…In these types of scaffolds, alignment of the newly regenerated tissue is not a major concern because of the nature of the tissue that should be reconstructed 56 . Electrospinning is another but highly expensive and timeconsuming technological approach 2,42,54 . By this technology, it is possible to align the polymerised fibres of the scaffold (Fig.…”
mentioning
confidence: 99%
“…12 Previous studies have shown that electrospun scaffolds made of polymers such as PLGA and Polydioxanone (PDO) exhibit excellent cellular response and biocompatibility. 13,14 It has also been reported that multilineage differentiation into osteoblasts, adipocytes, and chondrocytes is fully supported by an electrospun tissue scaffold. 15 Electrospun PLGA scaffolds have previously been shown to support successful differentiation of mesenchymal stem cells (MSCs) in vitro for the generation of bone, cartilage and dermal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that electrospun materials cause a lower immune response in vivo compare to the same material in plain sheets . Previous studies have shown that electrospun scaffolds made of polymers such as PLGA and Polydioxanone (PDO) exhibit excellent cellular response and biocompatibility . It has also been reported that multilineage differentiation into osteoblasts, adipocytes, and chondrocytes is fully supported by an electrospun tissue scaffold …”
Section: Introductionmentioning
confidence: 99%